Localized corrosion of the Mg alloys with inhibitor-containing coatings: SVET and SIET studies. (January 2016) - Gnedenkov, A.S.; Sinebryukhov, S.L.; Mashtalyar, D.V.; Gnedenkov, S.V.
Highlights: The way of self-healing coating formation on the Mg alloy has been suggested. SVET and SIET were used for determining the kinetics of the self-healing process. The self-healing mechanism has been studied and described in this work. Inhibitors ability to prevent the corrosion process in the defect zone was studied. Self-healing composite coating avert intensive destruction of the magnesium alloy. Abstract: The way of self-healing coating formation at the surface of magnesium alloys on the base of plasma electrolytic oxidation method (PEO) has been suggested. Scanning Vibrating Electrode Technique (SVET) and Scanning Ion-Selective Electrode Technique (SIET) were used for determining the kinetics and mechanism of the self-healing process. The treatment of the PEO-layer by the solution containing 8-hydroxyquinoline enables one to decrease the current density of the composite coating in 30 times (3.2 μA cm −2 ) in the corrosion-active environment in comparison with the base PEO-coating (100 μA cm −2 ) and avert the intensive destruction of the material.